Condições de Referência em riachos de cabeceira tropicais - Janaina Uchôa Medeiros Agra (2015)
The definition of Reference Conditions aims to quantify the natural variability of environmental and biological features in minimally disturbed ecosystems. The Upper Rio das Velhas basin (State of Minas Gerais, Brazil) is located in a transition zone which encompasses Rupestrian fields and Atlantic semi-deciduous forests, resulting in high environmental and biological variability. The objectives of this study were: (i) describe reference conditions of environmental and biological features in headwater streams at the Upper Rio das Velhas basin, based on (a) environmental measurements at multiple spatial scales, and (b) the structure of benthic macroinvertebrate communities; (ii) test the hypothesis that the composition, richness and abundance of benthic communities in areas of rupestrian fields and forests are different; (iii) point out which environmental variables best explain the variation in species richness of these communities. 21 headwater streams were selected in forest areas and 10 in rupestrian fields minimally altered by human activities. The streams were characterized at the micro-basin scale (e. g., altitude, lithology, drainage area), at reach scale (e. g., channel morphology, substrate type and flow) and also concerning the water chemistry. The physical habitats protocol of the US Environmental Protection Agency (US-EPA) was simplified and applied at the stream sites. We collected 19,295 macroinvertebrates, classified into 63 families. The composition and richness of macroinvertebrates were different between rupestrian fields and forests. Streams in forest have a greater number of taxa (29.9 ± 5.9) than rupestrian fiels streams (23.6 ± 6.3) (t = 2.69, df = 29, p = 0.012). A multiple linear regression model with three variables (electrical conductivity, embeddedness and concentration of nitrite) explained 42% of the richness variation among the streams. Electrical conductivity and embeddedness were positively correlated with taxa richness, while nitrite concentrations did the opposite. The study pointed out possible environmental factors driving the structure of macroinvertebrate communities in headwater streams. It also provides baseline data for future plans of monitoring and restoration of degraded streams, and propose a simplified protocol that can serve as an important monitoring tool for tropical headwater streams.